(untitled) (Research, Society and Development, 2021)
The objective was to verify the proportion of dentists in relation to the Angolan population, to undergraduate and graduate courses in dentistry, and to analyze the pedagogical projects of the existing courses. This is a descriptive, exploratory and documentary study that analyzed data on the population and the number of dentists in Angola, obtained through information from the National Statistics Institute and the Order of Doctors of Angola. An application for cell phones called “Qualificar”, made available by the Angolan government, was used to collect information about the existing courses. The websites of the Ministry of Higher Education, Science, Technology and Innovation; National Institute for Evaluation, Accreditation and Recognition of Higher Education Studies in Angola; and the National Press were consulted to collect data related to higher education in Angola. Information on pedagogical projects was obtained directly from Higher Education Institutions (HEIs). Angola has 701 dentists registered for a population of 30,175,553 inhabitants, that is, a proportion of 1/43,460. Among the eighty existing HEIs, only ten were authorized by the government to offer undergraduate courses in dentistry: six were located in the country’s capital and four were distributed in other provinces, with workload varying from 4,688 to 5,536 hours. It was concluded that of the seven academic regions in the country, 4 do not have courses in dentistry; the number of dentists is not compatible with the population of Angola; no HEI offered postgraduate courses in dentistry and there is no standardization of pedagogical projects among the existing undergraduate courses.